Pelatihan Pembuatan E-modul Berbasis Riset bagi Guru FISIKA di Kabupaten Takalar - Sudirman Sudirman; Ali Umar Dani; Herdianti Nursyamsi (Universitas Majalengka, 2023)
Research-based physics e-module is one of the science learning innovations that really helps science teachers in developing the quality of learning. Teaching materials in the form of e-modules have become a necessity in the science learning process at schools. There are various facilities for teachers and students as recommended by the Ministry of Education and Culture. There are still many science teachers who don't know how or the technique of making e-modules properly and correctly. Therefore, community service activities in the form of training in making research-based physics e-modules are very much needed. This training aims to broaden knowledge of science teachers, especially physics, regarding the technique of making e-modules properly and correctly. This training is expected to provide solutions to the problems faced by both teachers and students in the learning process.